TRANSFORMATIONS IN NATIONALIST POLITICS: THE POSITION OF THE NATIONALIST MOVEMENT PARTY IN TURKISH POLITICAL LIFE (Third Sector Social Economic Review, 2024)
In the 21st century, as the position and influence of nationalism on both society and actual politics in the world continues to strengthen, the roots and basic dynamics of the determinism of nationalism in Turkish politics should be examined. In doing so, it is necessary to analyze and compare the conceptions of nationalism in Türkiye in terms of both the historical process in political life and the theoretical framework. In order to make sense of the impact and determinism of nationalism on party politics and the political projection of social life, the direction and intensity of nationalist language in politics should be analyzed. The distinction between modern-secular nationalism and traditional nationalism comes to the fore here. In addition, more exclusionary and aggressive nationalisms centered on anti-immigrant sentiments, which have become more prominent especially towards the end of the first quarter of the 21st century, should also be examined and compared. Furthermore, it is important to make predictions and analyses not only about the present or the past, but also about how nationalism will be shaped in the second century of the republic.In the end, the study discusses the role of nationalism in Turkish political life in light of the current political conjuncture, taking into account the basic dynamics of the postmodern era. Without deviating from this scope, the fundamental dynamics of nationalist politics and, in particular, its transformations are addressed. While doing this, an attempt is made to conduct discourse analysis by focusing on the institutional publications of political parties. The study ut
Keywords: Turkish Political Life; Nationalism; Nationalist Movement Party; Identity